Positive Caregiving Styles Attenuating Effects of Cumulative Trauma Among Youth Who Commit Sexual Crimes. (December 2022) - Yoder, Jamie; Brown, Adam; Grady, Melissa; Dillard, Rebecca; Kennedy, Natalie
Among youth who commit sexual crimes, childhood trauma experiences have been linked to a host of outcomes including trauma symptom expression. Furthermore, research has begun assessing differential rates of cumulative adverse childhood experiences (ACEs) between youth who commit sexual and non-sexual crimes. Yet, few studies have comparatively examined rates of cumulative traumatic events using more robust measures of adversity. There is scant research on outcomes associated cumulative trauma among youth who commit sexual crimes including linkages to trauma symptoms and how positive parenting styles (PCSs) can attenuate in this relationship. This study aims to compare cumulative trauma experiences between youth who commit sexual ( n = 112) and non-sexual crimes ( n = 224). Among youth who commit sexual crimes, we test how PCSs mitigate or moderate the effects of cumulative trauma on trauma symptoms. Results from independent samples t -tests revealed significant group differences on singular and cumulative traumatic experiences, and trauma symptomatology, where youth who commit sexual crimes had higher rates of all. Stepwise linear regressions revealed mitigating effects of maternal PCSs and tests of moderation revealed main and interaction effects, where intermediate positive maternal caregiving styles for youth with higher cumulative trauma were associated with greater trauma symptomatology. Implications and limitations are discussed.